Social Labeling, Power, and Deviancy Amplification: Community Stigmatization of Migrant Residents in Adultery Cases in Banda Aceh - Mujtahid Mujtahid; Ali Sodiqin; Moch. Nur Ichwan (Journal of Islamic Law, 2025)
Existing research on social labeling in adultery (zinā) cases in Aceh remains limited, particularly in exploring how local power dynamics shape processes of stigmatization. This article examines how the social labeling of migrant residents (ureung tamong) accused of zinā operates as a mechanism of social control that reinforces the dominance of local residents (asoe lhok), while media exposure intensifies stigma through deviancy amplification. Employing a legal anthropological approach, the article is based on three months of fieldwork in Banda Aceh, involving participant observation, in-depth interviews with ten key informants—including village authorities, community leaders, law enforcement officers, and local residents—and analysis of relevant online and social media content. The findings reveal that social labeling in zinā cases is driven not only by religious and customary norms but also by underlying community power structures, rendering ureung tamong significantly more vulnerable to public exposure and social sanctions than asoe lhok. Additionally, digital media exacerbates the amplification of deviance, resulting in prolonged social exclusion of individuals who have already faced customary or formal legal punishment. The persistence of digital records further obstructs their reintegration into society. This article contends that social labeling functions not merely as a tool of moral regulation but also as a strategy for maintaining the dominance of powerful groups within the community. It concludes by calling for more inclusive media practices and legal policies to prevent the prolonged social and psychological marginalization of individuals in zinā cases who have fulfilled their legal obligations.